Exploring Factors Related to Completion of an Online Undergraduate-Level Introductory Statistics Course - Zimmerman, Whitney Alicia; Johnson, Glenn (Online Learning, 2017)
Data were collected from 353 online undergraduate introductory statistics students at the beginning of a semester using the Goals and Outcomes Associated with Learning Statistics (GOALS) instrument, an abbreviated form the Statistics Anxiety Rating Scale (STARS), a survey of expected grade and expected time commitment, and the first lesson quiz. At the end of the semester, whether or not each student successfully completed the course with a grade of D or higher was recorded. It was hypothesized that students who successfully completed the course would have had favorable ratings on each of these variables. While there were no significant differences between students who did and did not successfully complete the course in terms of anxiety, attitudes, or expected time commitment, students who completed the course had higher scores on the GOALS, higher expected grades, and higher scores on the first quiz of the semester. Stepwise logistic regression found that students’ attitudes towards statistics teachers and scores on the first quiz of the semester could be used to predict whether or not students would successfully complete the course. Based on these findings, suggestions for online instructors are given.